Changes in CA 125 Level Pre and Post Ovarian Cancer Surgery - Aprivinta, Sherlyana Mega; Pradjatmo, Heru; Hadiati, Diah Rumekti (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Ovarian cancer is one of the gynecological cancers that has a fairly high mortality rate and has a poor prognosis. Ovarian cancer management includes optimal operation followed by chemotherapy, which at follow up will have an effect on decreasing CA 125 levels. But in fact there are several studies showing increased CA 125. Given these differences in findings, this study attempted to evaluate the pre and post operation changes in CA 125 levels in ovarian cancer patients.Objective: This study aims to determine the changes in pre and post operation CA 125 levels in ovarian cancer patients. And to find out the optimal relationship between CA 125 level post operation and post operation.Methods: The type of research is an analytic study with a prospective cohort design. The source comes from secondary data taken from Simetris dr. Sardjito Hospital within 6 months.Results: The distribution of the age < 40 years was 11 and 19 were 40 years old. There was a significant change in pre operation log CA 125 levels (mean = 2,53 or 902,03U/ml) and post operation log CA 125 levels (mean = 1,92 or 406,23 U/ml). With a difference or delta mean of 0,61 or 495,80 U/ml and p value = 0.001. There was a significant difference in post operation log CA 125 levels between optimal and non optimal operation. Based on risk factors, there was a significant change or decrease in log CA 125 levels pre and post operation, but there was no significant difference in log CA 125 levels pre and post operation.Conclusion: There was a significant decrease in log CA 125 levels pre and post operation in patients with ovarian cancer who underwent operation. The post operation log CA 125 level in optimal operation is lower than in non-optimal operation.Keywords: CA 125, Ovarian Cancer, Operation, Optimal